2013
DOI: 10.1016/j.phytochem.2013.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Inducibility of chemical defences by two chewing insect herbivores in pine trees is specific to targeted plant tissue, particular herbivore and defensive trait

Abstract: There is increasing evidence that plants can react to biotic aggressions with highly specific responses. However, few studies have attempted to jointly investigate whether the induction of plant defences is specific to a targeted plant tissue, plant species, herbivore identity, and defensive trait. Here we studied those factors contributing to the specificity of induced defensive responses in two economically important pine species against two chewing insect pest herbivores. Juvenile trees of Pinus pinaster an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 56 publications
(76 reference statements)
5
57
0
Order By: Relevance
“…; Moreira et al . ). A consequence of the discovery that herbivore elicitors drive plant chemical induction has been a shift in the experimental methodology of these studies to exclude ‘herbivory’ treatments that involve only mechanical damage to simulate herbivory.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Moreira et al . ). A consequence of the discovery that herbivore elicitors drive plant chemical induction has been a shift in the experimental methodology of these studies to exclude ‘herbivory’ treatments that involve only mechanical damage to simulate herbivory.…”
Section: Discussionmentioning
confidence: 97%
“…; Moreira et al . ). In contrast, almost nothing is known about specificity in the induction of physical defence traits, and many studies simulate herbivory using artificial damage without the application of herbivore elicitors or jasmonates (Gibson, Bazely & Shore ; Abdala‐Roberts & Parra‐Tabla ; Valkama et al .…”
Section: Introductionmentioning
confidence: 97%
“…Our results showed that there is herbivore specificity of plant–plant communication, because herbivore resistance on receiver Baccharis salicifolia plants increased only when emitter and receiver plants were attacked by the same aphid species. Specificity of induced defences against herbivores has been found across several plant–herbivore systems (Agrawal, ; Bingham & Agrawal, ; Xiao et al ., ; Moreira et al ., , ; Rowen & Kaplan, ). Such specificity could have evolved by means of natural selection, and may thus be adaptive (Bingham & Agrawal, ).…”
Section: Discussionmentioning
confidence: 99%
“…Both P. sylvestris and P. abies responses to MeJA included accumulation of ( − )-β-pinene in phloem, a stress response observed in several conifer species to various treatments (Gould et al 2009; Moreira et al 2013; Persson 2003; Sampedro et al 2010). In P. abies , ( − )-α-pinene was induced at the same time as ( − )-β-pinene, possibly due to activation of ( − )α/β-pinene synthase (Martin et al 2004).…”
Section: Discussionmentioning
confidence: 99%